Pendekatan supply chain operations reference dan fuzzy quality function deployment untuk peningkatan kinerja rantai pasok minuman lidah buaya - Nurimansyah Nurimansyah; Wike Agustin Prima Dania; Arif Hidayat (AGROINTEK, 2024)
Pontianak is Indonesia's largest Aloe vera producer, with several SMEs that process Aloe vera into food and beverage products. SME XYZ stands as one of the major SMEs in the city of Pontianak. The continuous emergence of competitors and complaints from retailers unsatisfied with the provided services have compelled SME XYZ to identify the root causes of these issues. Subsequently, they must determine various solutions for performance improvement. However, in reality not all input variables can be numerated so that they must be developed into linguistic variables expressed in fuzzy because it is considered more appropriate to describe the input obtained form consumer desires so that it can be used as input to the system. This research aims to identify and map the desired retailer needs using the Supply Chain Operation Reference (SCOR) method. The goal is to provide a performance improvement strategy using the Quality Function Deployment (QFD) method to meet retailer desires and requirements.  Data collection techniques involve conducting interviews and questionnaires with retailers and SME XYZ and conducting thorough literature studies. The research results reveal that retailers use 13 Key Performance Indicators (KPIs) to assess SME XYZ. The highest priorities for retailers regarding SME XYZ include consistent product quality, prompt handling of complaints, the ability to fulfill unexpected orders, and quality assurance certification. The top priority KPI for SME XYZ's improvement is the development of attractive product packaging. Within this context, SME XYZ provides seven technical responses to meet retailer needs. The most critical technical response, rated at 7.74, revolves around enhancing producer competence.